A highly selective and biocompatible chemosensor for sensitive detection of zinc(ii). (10th December 2015) - Dey, Sudipto; Roy, Ankita; Maiti, Guru Prasad; Mandal, Sushil Kumar; Banerjee, Piyali; Roy, Partha
Abstract : A selective fluorescence chemosensor for Zn 2+ has been developed with a very low limit of detection value (0.832 nM). Abstract : 2-Formyl-4-methyl-6-(2-benzoimidazolyliminomethyl)phenol (HL 1 ) has been synthesized via Schiff-base condensation between 4-methyl-2, 6-diformylphenol and 2-aminobenzimidazole in a 1 : 1 ratio in acetonitrile and characterized using elemental analysis and different spectroscopic methods. HL 1 has been found to be a selective fluorescence sensor for Zn 2+ ions. The emission intensity of HL 1 at 528 nm in 10 mM HEPES buffer in water : methanol (1 : 9, v/v) (pH = 7.2) increases in the presence of Zn 2+ when it is excited at 445 nm. Other metal ions can induce a slight increment or lowering of emission intensity. The spectral properties of HL 1 and 2-formyl-4-methyl-6-(2-benzoimidazolylmethyliminomethyl)phenol (HL 2 ) have been compared. It has been found that the presence of the methylene group in HL 2 can have a significant effect on the absorption and fluorescence peak positions of the Schiff-base molecule and its zinc complex. Some theoretical calculations have been done to get a better view into the different spectral transitions. HL 1 and HL 2 have been found to be highly sensitive towards the detection of Zn 2+ ions with very low LOD values. Excitation in the visible region and the effect of pH on the emission intensity of HL 1 encourage us to carry out biological studies. HL 1 has been used for human lung cancer cell (A549) imaging without cytotoxicity.